2008
DOI: 10.1038/aps.2008.3
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal bacillus Calmette–Guérin vaccination inhibits de novo allergic inflammatory response in mice via alteration of CD4+CD25+ T-regulatory cells

Abstract: Neonatal BCG vaccinations ameliorate de novo local eosinophilic inflammation induced by allergen and increase the numbers of CD4+CD25+ Treg cells and Foxp3 expression. The cell-cell contact inhibition and regulatory cytokine production may be involved in the regulatory mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…These results demonstrated that C-K regulated the T cell response by inhibiting the differentiation and activation of CD4 + T cells instead of reducing the number of CD4 + T cells. Tregs control the responses of APCs and effector T cells in the periphery through direct interaction with these cells or through anti-inflammatory cytokine production, and they play an important role in limiting inflammation and regulating adaptive immunity [43,44] . C-K restored the percentage of Tregs, which may be one of the mechanisms underlying the anti-CIA effects of C-K as well as its anti-inflammatory and immunosuppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that C-K regulated the T cell response by inhibiting the differentiation and activation of CD4 + T cells instead of reducing the number of CD4 + T cells. Tregs control the responses of APCs and effector T cells in the periphery through direct interaction with these cells or through anti-inflammatory cytokine production, and they play an important role in limiting inflammation and regulating adaptive immunity [43,44] . C-K restored the percentage of Tregs, which may be one of the mechanisms underlying the anti-CIA effects of C-K as well as its anti-inflammatory and immunosuppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…47 BCG vaccination has long been known to be a potent inducer of IFN-g-secreting Th1 responses and Tregs. 15,48,49 The increase in the levels of circulating immune factors (e.g., cytokines, chemokines or other factors), many of which can enter the CNS. These immune factors may promote microglia activation and proliferation and thus increasing the expression of neurotrophins.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, vaccination of mice with bovis Bacille Calmette–Guérin (BCG) or recombinant BCG expressing house dust mite protein Derp, reduced subsequent allergic airway inflammation after OVA or Derp sensitization and challenge, respectively. In addition, increased numbers of Foxp3+ cells in the lung and enhanced expression of CTLA-4 and elevated levels of IL-10 and TGF-b were observed (95, 96). Instead, infection early in life with respiratory syncytial virus (RSV) impaired Treg function and exacerbated allergic airway inflammation in mice (97).…”
Section: Treg Cells In the Lungmentioning
confidence: 99%